Flexible Graphene Electrode-Based Organic Photovoltaics with Record-High Efficiency. (16th September 2015) - Park, Hyesung; Chang, Sehoon; Zhou, Xiang; Kong, Jing; Palacios, Tomas; Gradecak, Silvija
Abstract : Advancements in the field of flexible high-efficiency solar cells and other optoelectronic devices will strongly depend on the development of electrode materials with good conductivity and flexibility. To address chemical and mechanical instability of currently used indium tin oxide (ITO), graphene has been suggested as a promising flexible transparent electrode, but challenges remain in achieving high efficiency of grahene-based polymer solar cells (PSCs) compared to their ITO-based counterparts. Here we demonstrate graphene anode- and cathode-based flexible PSCs with record-high power conversion efficiencies of 6.1% and 7.1%, respectively. The high efficiencies were achieved via thermal treatment of MoO3 electron blocking layer and direct deposition of ZnO electron transporting layer on graphene. We also demonstrate graphene-based flexible PSCs on polyethylene naphthalate substrates and show the device stability under different bending conditions. Our work paves a way to fully graphene electrode-based flexible solar cells using a simple and reproducible process